Life After Guns - Hardgrove, Abby (Rutgers University Press, 2021)
Life After Guns explores how ex-combatants and other post-war youth negotiated a depleted and difficult social and cultural landscape in the years following Liberia’s fourteen-year bloody civil war. Unlike others who study child soldiers, Abby Hardgrove’s ethnography looks at both former combatants and also the youth who were not recruited to fight. She focuses on the structural constraints and household and family organizations that either helped or limited opportunities as these young men grew into adulthood. Whether young men fought or not, and whether they had cultural capital before the war or not, family relations mattered a great deal in how they fared after the war.